Модернізований очисний пристрій - Дубовець, Олексій Миколайович; Подустов, Михайло Олексійович; Литвиненко, Євгенія Ігорівна; Пугановський, Олег Валентинович (НТУ "ХПІ", 2016)
Представлены результаты разработки, содержащие питательный и отводящий патрубки, приемную емкость, двигатель, вал, очистительный орган, выполненный из набора плоских колец с крестовиной, установленных на валу двигателя параллельно друг другу на расстоянии, величина, которого определяется калиброванными шайбами с квадратным отверстием. Ширина колец определяется по формуле b = (0,30–0,35)R. Сборный цилиндрический бункер с неподвижным горизонтальным бортом, отличается тем, что на верхней крышке двигателя установлена неподвижная ось, а на боковой закреплен очистительный орган.

The results of the development, containing nourishing and outlet pipes, the receiving capacity, motor shaft, cleansing the body is made of a set of flat rings with the crossbar installed on the motor shaft parallel to each other at a distance, the value of which is determined by calibrated washers with square hole and the width rings given by b = (0,30–0,35)R and collective cylinder tank with a fixed horizontal board, characterized in that the top cover of the engine installed fixed axis, and on his side secured purifying body consisting of block rotation shaft and ejector made of spring wire, with the motor shaft, the shaft axis and rotation unit cinematically connected by gears and ejector fixed to the shaft rotation unit so that their maximum input into annular gap formed by movable and immovable elements of cleansing the body, selected in accordance with the condition ℓ = (0,6–0,7)b, where ℓ – maximum input ejector during their rotation annular gap clearing agency, b – width of a flat ring.
Upgraded cleaning device
Keywords: системи автоматичного контролю; забруднення; вимірювальні прилади; контрольно-вимірювальні прилади; виштовхувачі